2018
DOI: 10.3311/ppci.12708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exhaust Gas on Natural Stone Tablets, a Laboratory Experiment

Abstract: 8 different natural stone types were exposed to exhaust gas under laboratory conditions to assess urban stone damage. 3 cm in diameter cylindrical test specimens were made from travertine, non-porous limestone, limestone, rhyolite tuff, sandstone, andesite, granite and marble. The samples were exposed for 1, 2, 4 and 8 hours to exhaust gas that was generated by compression ignition internal combustion engine. The exhaust emission was measured. The operating conditions of the engine were documented and several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Higher biological colonization has also been observed on more porous types, with worse results for limestone than for marble [10] and for limestone than granite [59]. The penetration of soot was found [64] to be higher for the more porous lithologies (rhyolite tuff, travertine, granite and the more porous limestone) while deep penetration of particles was not observed by visual inspection on other rocks with more dense structure (andesite, marble, sandstone, and a less porous limestone). There is a report of higher susceptibility to sulfation of travertine than marble, being the porosity of the travertine higher [54].…”
Section: Pore Network Featuresmentioning
confidence: 98%
See 1 more Smart Citation
“…Higher biological colonization has also been observed on more porous types, with worse results for limestone than for marble [10] and for limestone than granite [59]. The penetration of soot was found [64] to be higher for the more porous lithologies (rhyolite tuff, travertine, granite and the more porous limestone) while deep penetration of particles was not observed by visual inspection on other rocks with more dense structure (andesite, marble, sandstone, and a less porous limestone). There is a report of higher susceptibility to sulfation of travertine than marble, being the porosity of the travertine higher [54].…”
Section: Pore Network Featuresmentioning
confidence: 98%
“…We can include in these considerations also a study that presented observations of slight bowing of magmatic rocks under thermal cycles [51]. There are also studies explaining mass loss in tuff and andesite as resulting from mineralogical changes associated with loss of interstitial water of layered minerals because of gas temperature under conditions simulating atmospheric pollution [64].…”
Section: Minerals and Other Phase Constituentsmentioning
confidence: 99%
“…The geochemical content of natural archives such as ice, marine sediment, and peat are often studied to investigate changing levels of anthropogenic pollution through time. Such studies exploit, among other tracers, the immobility of lead (Pb) in the environment, , interpreting changing Pb concentrations and/or isotopic ratios as indicators of changing levels and/or sources of air pollution. , An additional archive that is less frequently examined is stone weathering crusts. Pb concentrations in weathering crusts of historic urban built structures typically range from ten to hundreds of parts per million (ppm), reaching up to thousands of ppm when in the vicinity of industrial sites. This poses problems when Pb, together with other carcinogenic and toxic components, is remobilized and reintroduced into the overall urban pollution budget through processes such as cleaning (e.g., sandblasting), fire, weathering of surface coating such as lead-based paint, and common surface erosion. Indeed, recent studies on urban heavy metal dust have found an increasing risk to the environment and human health due to such remobilization of Pb. Therefore, there is an urgent need to advance our understanding of the interactions between the historic built environment and both ongoing and past environmental pollution accumulated in weathering crusts.…”
Section: Introductionmentioning
confidence: 99%
“…Flooding in nuclear waste packs occurs as a result of water diffusion via capillary absorption, which is also a process that influences water diffusion across different rock densities, surface tension, and the angle of contact [7]. Additional criteria should be explored in order to forecast water absorption levels, including the porosity, rhyolitic tuff, and the density of stones [8].…”
Section: Introductionmentioning
confidence: 99%